Exercise Training and Beta-Alanine-Induced Muscle Carnosine Loading - Bex, Tine; Chung, Weiliang; Baguet, Audrey; Achten, Eric; Derave, Wim (Frontiers in Nutrition, 2015)
Purpose. Beta-alanine (BA) supplementation has been shown to augment muscle carnosine concentration, thereby promoting high-intensity exercise performance. Trained muscles of athletes have a higher increase in carnosine concentration after BA supplementation compared to untrained muscles, but it remains to be determined whether this is due to an accumulation of acute exercise effects or to chronic adaptations from prior training. The aim of the present study was to investigate whether high-volume (HV) and/or high-intensity (HI) exercise can improve BA-induced carnosine loading in untrained subjects. Methods. All participants (n=28) were supplemented with 6.4 g/day of BA for 23 days. The subjects were allocated to a control group, HV or HI training group. During the BA supplementation period, the training groups performed 9 exercise sessions consisting of either 75–90 min continuous cycling at 35–45% Wmax (HV) or 3 to 5 repeats of 30s cycling at 165% Wmax with 4 min recovery (HI). Carnosine content was measured in soleus and gastrocnemius medialis by proton magnetic resonance spectroscopy. Results. There was no difference in absolute increase in carnosine content between the groups in soleus and gastrocnemius muscle. For the average muscle carnosine content, a higher absolute increase was found in HV (+ 2.95 mM; P = 0.046) and HI (+ 3.26 mM; P = 0.028) group compared to the control group (+ 1.91 mM). However, there was no additional difference between the HV and HI training group. Conclusions. HV and HI exercise training showed no significant difference on BA-induced muscle carnosine loading in soleus and gastrocnemius muscle. It can be suggested that there can be a small cumulative effect of exercise on BA supplementation efficiency, although differences did not reach significance on individual muscle level.